Гистогенез соединительнотканных структур сердца свиньи домашней в процессе антенатального развития. Сообщение I - Павлов, Г.Г. (Вестник зоологии, 1973)
Histogenesis of the heart connective-tissue structures developing from its endocardiac anlage is described on the basis of morphological and histochemical studies of hearts in 40 embryos of Sus domesticus from the third to the sixteenth weak of antenatal development (from 16 to 246 mm long).

20 G. G. Pavlov
Three types of cells are distinguished in endocardiac pulvilla, valves and a fibrous ring: embryonal mycogenic, fibroblasts and histocytes. It is stated that beginning from the third week of antenatal development the embryonic mutogenic cells penetrate into the myocardium from the fibrous ring region and take part in formation of the connectivetissue myocardium stroma.
In the heart connective-tissue structures developing from its endocardiac anlage (parietal endocard, endocardiac pulvilla, valves and a fibrous ring) hyaluronic acid and chondroitinsulphate C were found histochemically beginning from the third week of antenatal development and chondroitinsulphate from the eighth week.